Cultural transformation at enterprise level: Case study evidence from Poland - Izabela Robinson; Beata Tomczak-Stepien (Journal for East European Management Studies, 2000)
This paper presents an analysis of the business cultures of four post-socialist Polish enterprises. Western capitalist orthodoxy emphasises the development and management of an appropriate organisational culture as a key component of organisational effectiveness. Within an East European context it is likewise suggested that the development of appropriate market behaviours is necessary if transforming economies are not to hit a ceiling of recovery. However, what constitutes an 'appropriate' organisational culture within an East European context is open to speculation and debate, particularly if it accepted that there is no dominant model of capitalist work organisation which might represent a template for transforming economies. This paper draws on empirical case study material to appraise the business cultures of four post-socialist Polish enterprises. Findings suggest that ownership, turnover of human capital and management philosophy and ideology represent key factors in the development of market oriented behaviours. However, findings also reinforce the strength and endurance of the socialist culture. – – In dieser Arbeit wird die Analyse der Unternehmenskultur von vier polnischen Unternehmen der post-sozialistischen Ära vorgestellt. Was unter einer 'angemessenen' Organisationskultur im Osteuropäischen Kontext zu verstehen ist, darüber kann spekuliert und debattiert werden, besonders dann, wenn kein Standardmodell kapitalistischer Arbeitsorganisation für sich wandelnde Ökonomien existiert. Die Ergebnisse der vorliegenden empirischen Studie legen die Vermutung nahe, daß Eigentum, Humankapital, Managementphilosophie und Ideologie Schlüsselfaktoren bei der Herausbildung marktorientierten Verhaltens darstellen. Andererseits bestätigt sich die nachhaltige Wirksamkeit der sozialistischen Kultur.
Keywords: 650